El Croquis Night: Excursus into Nocturnal Obliteration in Architectural Media - Contreras, Javier Fernández (Interiority, 2021)
El Croquis is one of the most prestigious architectural magazines in the world. Founded in 1982 by Richard Levene and Fernando Marquez, it publishes five monographs every year. The volumes dedicated to established Pritzker Prize names like OMA Rem Koolhaas, SANAA Sejima & Nishizawa, Herzog & de Meuron, Alvaro Siza or Rafael Moneo, are considered their respective oeuvre complète. The journal almost never publishes nocturnal photographs of interior spaces. The same goes for other major architecture magazines. In February 2020, HEAD – Genève invited Richard Levene to create a night edition of El Croquis. The workshop focused on the idea that night is a forgotten paradigm in the construction of modern and contemporary architectural discourse.